Political relations between Israel and its Arab citizens since 2000 - Egbuta, Ifeanyi Dennis (Πανεπιστήμιο Πελοποννήσου, 2017)
The aim of this paper is to analyze the political relations between Israel and its Arab citizens since 2000, identifying areas of Arab participation in the politics of the state and clarifying claims of marginalization and oppression by the state. This paper would analyze the political framework of Israel, the base on which the political system of the state was established, which has determined its features. The extent of Arab participation in Israeli politics would be examined, as well as the issues surrounding marginalization, inclusion and equality in the political arena of the state. The relations between the Arab minority and the Jewish majority which largely controls the state would be analyzed, using current events and survey results, to determine the perception both harbour toward each other, how it has improved or deteriorated since 2000. The latter part would investigate how the state's policies have affected the Arab minority and their reaction toward these policies. In conclusion, taking note of the conditions under which the state was established as a homeland for the Jews, making it a Jewish state, and its status as a democratic state, the hegemony of the Jews is clarified, meanwhile the constitutional rights of the Arabs as citizens have been upheld in accordance to the Israeli Proclamation of Independence. Considering the tense relations between the state and its Arab citizens, this paper recommends necessary compromise and efforts from both sides to gain each others’ trust and to ensure a cordial and progressive relation between the two.
Πολιτικές σχέσεις μεταξύ του Ισραήλ και των αραβικών πολιτών του από το 2000
Keywords: Ισραήλ--Πολιτική και διακυβέρνηση; Ισραήλ--Σχέσεις--Παλαιστίνη; Αραβο-Ισραηλινοί; Ισότητα; Δημοκρατία; Ισραηλινό πολιτικό σύστημα; Αραβική μειονότητα